PEMBUATAN SENYAWA METIL ESTER YANG DITURUNKAN DARI DARI MINYAK BIJI BINTARO (Cerbera manghas L.) SEBAGAI BAHAN BAKU DASAR PEMBUATAN SURFAKTAN - Ilham Burhanuddin; Daniel Daniel; Erwin Erwin (JURNAL KIMIA MULAWARMAN, 2019)
Synthesis methyl ester can be formed from kernel bintaro oil (Carberra Mangas L.) with two stages which is esterification and trans-esterification. The test result of methyl ester of bintaro kernel oil have iod value 92,82 g iod/100 gr oil, acid value 1,67 mg KOH/g oil with acid concentration 12,470% and saponification value 185.225 mg KOH/gr oil. From GC-MS analysis fatty acid dominant composition from methyl ester is methyl oleat with walue 45.86%. From HLB analysis show value 0,539. Result of analysis of FT-IR show methyl ester from bintaro kernel oil have typical absorbtion peak on wave number 17443.65 (C=O Ester).